2010
DOI: 10.1371/journal.pntd.0000742
|View full text |Cite
|
Sign up to set email alerts
|

Farm-Level Risk Factors for Fish-Borne Zoonotic Trematode Infection in Integrated Small-Scale Fish Farms in Northern Vietnam

Abstract: BackgroundNorthern Vietnam is an endemic region for fish-borne zoonotic trematodes (FZT), including liver and intestinal flukes. Humans acquire the FZT infection by eating raw or inadequately cooked fish. The production of FZT-free fish in aquaculture is a key component in establishing a sustainable program to prevent and control the FZT transmission to humans. Interventions in aquaculture should be based on knowledge of the main risk factors associated with FZT transmission.Methodology/Principal FindingsA lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 14 publications
1
76
0
4
Order By: Relevance
“…Poor sanitation and traditional methods of food preparation have accelerated the spread of food-borne trematode infection (PHAN et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Poor sanitation and traditional methods of food preparation have accelerated the spread of food-borne trematode infection (PHAN et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…(3) Although human fecal material is not deliberately used for fertilizing rice fields, the drainage system present in rural villages leads directly to the contamination of fields with human and animal feces. 16,37 The surprisingly high prevalence that we detected has important implications for the transmission potential of O. viverrini and therefore, the possible increases in opisthorchiasis and CCA in the lower Mekong Region. Our results showing that there is a higher ratio of infected snails in Lao PDR compared with Thailand fit the epidemiological findings that humans in the Nam Ngum wetland have very high prevalence of O. viverrini, whereas control efforts have been underway in Thailand for several decades, possibly reducing the contamination of the environment with infected feces.…”
Section: Resultsmentioning
confidence: 85%
“…M. tuberculata is the primary host for intestinal trematodes in aquaculture ponds i.e., mainly Haplorchis spp., Stellantchasmus falcatus, and C. formosanus (Phan et al 2010a). The black carp is primarily molluscivorous and most fish ponds have a dense population of viviparid snails, in particular, A. polyzonata.…”
Section: Discussionmentioning
confidence: 99%
“…Trematodes, particularly intestinal trematodes of family Heterophyidae, but also to some extent liver trematodes (Opisthorchis viverrini Stiles & Hassall, 1896 and Clonorchis sinensis Looss, 1907) of family Opisthorchiidae, may be found in aquaculture ponds in Vietnam (Le 2000;De 2004;Dung et al 2007;Phan et al 2010a) where eating raw fish is a common practice (Chi et al 2009;Phan et al 2011). Dung et al (2007) found from fecal examination that 64.9% of the adult people in Nam Dinh were positive for small trematode eggs (Heterophyidae and Opisthorchiidae) and expulsion of adult trematodes from 33 people with high egg counts (>1000 eggs/g feces) showed that 51.5% were infected with C. sinensis.…”
mentioning
confidence: 99%